2012
DOI: 10.1667/rr2749.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression-Based Detection of Radiation Exposure in Mice after Treatment with Granulocyte Colony-Stimulating Factor and Lipopolysaccharide

Abstract: In a large-scale nuclear incident, many thousands of people may be exposed to a wide range of radiation doses. Rapid biological dosimetry will be required on an individualized basis to estimate the exposures and to make treatment decisions. To ameliorate the adverse effects of exposure, victims may be treated with one or more cytokine growth factors, including granulocyte colony-stimulating factor (G-CSF), which has therapeutic efficacy for treating radiation-induced bone marrow ablation by stimulating granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
1
18
2
Order By: Relevance
“…Expression of GADD45a, LIG1 and XPC were decreased at 24 hours after 6 Gy IR in mice, whereas we observed increased expression at 24 hrs after 2 Gy in our ex vivo human blood culture model consistent with published human ex vivo and in vivo literature [7], [12], [30]. Also, our use of a 2 Gy exposure (rather than 6 Gy used in a prior mouse study [30]) is more relevant for radiation biodosimetry because individuals having a radiation exposure dosage of less than 2 Gy require no immediate treatment as opposed to those having a dosage higher than 2 Gy. The inherent differences between murine and human assays emphasize the importance of using human model systems to validate biomarkers for human radiation biodosimetry.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Expression of GADD45a, LIG1 and XPC were decreased at 24 hours after 6 Gy IR in mice, whereas we observed increased expression at 24 hrs after 2 Gy in our ex vivo human blood culture model consistent with published human ex vivo and in vivo literature [7], [12], [30]. Also, our use of a 2 Gy exposure (rather than 6 Gy used in a prior mouse study [30]) is more relevant for radiation biodosimetry because individuals having a radiation exposure dosage of less than 2 Gy require no immediate treatment as opposed to those having a dosage higher than 2 Gy. The inherent differences between murine and human assays emphasize the importance of using human model systems to validate biomarkers for human radiation biodosimetry.…”
Section: Discussionsupporting
confidence: 90%
“…However, in that study DDB2 was downregulated and no significant changes were observed for FDXR or XPC, which is inconsistent with our results and those of others in humans irradiated ex vivo [10]. Expression of GADD45a, LIG1 and XPC were decreased at 24 hours after 6 Gy IR in mice, whereas we observed increased expression at 24 hrs after 2 Gy in our ex vivo human blood culture model consistent with published human ex vivo and in vivo literature [7], [12], [30]. Also, our use of a 2 Gy exposure (rather than 6 Gy used in a prior mouse study [30]) is more relevant for radiation biodosimetry because individuals having a radiation exposure dosage of less than 2 Gy require no immediate treatment as opposed to those having a dosage higher than 2 Gy.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations